2016
DOI: 10.1002/pros.23164
|View full text |Cite
|
Sign up to set email alerts
|

Silodosin inhibits prostate cancer cell growth via ELK1 inactivation and enhances the cytotoxic activity of gemcitabine

Abstract: ELK1 is likely to be activated in prostate cancer cells and promote tumor progression. Furthermore, silodosin that inactivates ELK1 in prostate cancer cells not only inhibits their growth but also enhances the cytotoxic activity of gemcitabine. Thus, ELK1 inhibition has the potential of being a therapeutic approach for prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 31 publications
2
17
2
Order By: Relevance
“…Consistent with in vitro and in vivo animal findings in PCa, classical α-antagonists and their analogues appear to have broad activity, exhibiting cytotoxicity in other cancer cell lines including urogenital [44,65,66,67,68,69,70,71,72,73,74], gastrointestinal [73,74,75,76,77], lung [74,78], blood [79], brain [80,81] and thyroid [82]. Importantly, the cytotoxic and anti-proliferative effects are supported by several in vivo mice studies [48,66], suggesting ubiquitous anticancer actions of these drugs.…”
Section: Discussionsupporting
confidence: 58%
“…Consistent with in vitro and in vivo animal findings in PCa, classical α-antagonists and their analogues appear to have broad activity, exhibiting cytotoxicity in other cancer cell lines including urogenital [44,65,66,67,68,69,70,71,72,73,74], gastrointestinal [73,74,75,76,77], lung [74,78], blood [79], brain [80,81] and thyroid [82]. Importantly, the cytotoxic and anti-proliferative effects are supported by several in vivo mice studies [48,66], suggesting ubiquitous anticancer actions of these drugs.…”
Section: Discussionsupporting
confidence: 58%
“…ELK1 regulates various cell processes, including cell proliferation and apoptosis, and can be regulated by miRNAs 42 . ELK1 and pELK-1 expression have been positively associated with several types of cancer, including breast cancer, colonic adenocarcinoma, and prostate cancer 43 45 . MiR-150 could regulate ELK1 expression, and ELK1 knockdown could abolish the anti-apoptotic effect of the inhibitor miR-150 in endothelial cells 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that Elk1 plays an important role in cancer progression. Kawahara et al found that Elk1 is induced in prostate cancer and promotes tumor development, whereas Elk1 inhibition suppresses tumor growth (44). Additionally, Elk1 is upregulated and promotes cell proliferation in bladder cancer and non-small cell lung cancer (NSCLC) (10).…”
Section: Discussionmentioning
confidence: 99%